Factors explaining the spatial agglomeration of the Creative Class. Empirical evidence for German artists - Christoph Alfken; Tom Broekel; Rolf Sternberg (Philipps-University Marburg, Department of Geography, 2013)
The paper contributes to the ongoing debate about the relative importance of economic and amenity-related location factors for attracting talents or members of the creative class. While Florida highlights the role of amenities, openness, and tolerance, others instead emphasize the role of regional productions systems, local labour markets and externalities. The paper sheds light on this issue by analysing changes in the spatial distribution of four groups of artists over time: visual artists, performing artists, musicians, and writers. Little evidence is found for amenity-related factors influencing the growth rates of regional artist populations. Moreover, artists are shown to be a heterogeneous group inasmuch as the relative importance of regional factors significantly differs between artist branches.
Keywords: O31; O18; R12; 330; Artists; bohemians; creative class; spatial dynamics; amenities; agglomeration